ANALISIS KESALAHAN SISWA SMA DAN SMK PADA MATERI BANGUN RUANG SISI DATAR BERDASARKAN KEMAMPUAN SPASIAL SISWA - Geraldi Valeska Heryadi Putra; Rippi Maya; Ratni Purwasih; Nelly Fitriani; Puji Nurfauziah (IKIP Siliwangi, 2022)
In this study, the purpose of analyzing how students' mistakes in building flat side rooms based on spatial abilities. This type of research is descriptive and qualitative. The sample used was 4 students which included 2 high school students in class XII with female gender, and 2 students of SMK class XII with male gender. The data collection technique is in the form of an instrument with a spaceability test, which consists of 4 description questions. The analysis technique used is based on watson criteria. Referring to Watson's criteria, students still make 4 mistakes caused due to several internal and external factors, these errors include incorrect data, improper procedures, skill hierarchy problems, and errors other than the seven above.